2008
DOI: 10.1097/gim.0b013e3181809613
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor polymorphisms and susceptibility to hypertension: A HuGE review

Abstract: The angiotensin II type 1 receptor (AGTR1) plays an integral role in blood pressure control, and is implicated in the pathogenesis of hypertension. Polymorphisms within this gene have been extensively studied in association with hypertension; however, findings are conflicting. To clarify these data, we conducted a systematic review of association studies of AGTR1 polymorphisms and hypertension, and performed a meta-analysis of the rs5186 variant. Results show that the currently available literature is too hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 178 publications
0
39
0
1
Order By: Relevance
“…Angiotensin II receptor type-1 (AGTR1) is a G-protein coupled receptor for angiotensin II, especially in the heart and kidney, and has been studied in many health conditions, including heart failure and stroke (Henskens et al, 2007;Wu et al, 2009). AGTR1 polymorphisms are associated with the susceptibility to hypertension and prehypertension in the American population (Mottl et al, 2008;Fung et al, 2011). A meta-analysis also found that the AGTR1 variant has been associated with an increased risk of hypertension in the Chinese population (Levy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II receptor type-1 (AGTR1) is a G-protein coupled receptor for angiotensin II, especially in the heart and kidney, and has been studied in many health conditions, including heart failure and stroke (Henskens et al, 2007;Wu et al, 2009). AGTR1 polymorphisms are associated with the susceptibility to hypertension and prehypertension in the American population (Mottl et al, 2008;Fung et al, 2011). A meta-analysis also found that the AGTR1 variant has been associated with an increased risk of hypertension in the Chinese population (Levy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that it might affect mRNA stability and transcription, or alternatively be in linkage disequilibrium with other polymorphisms. 53,54 It is well known that China comprises the largest geographical span, the highest number of ethnic groups and the most languages of East Asia. 55 Usually, Chinese living north of the Yangtze River are described as Northern Chinese and ones living south of the Yangtze River are Southern Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…14 The association to essential hypertension is, however, controversial. 15 Some studies have also examined the potential relationship between this SNP and preeclampsia. Most, but not all of these studies, failed to find an association.…”
mentioning
confidence: 99%